Processes of Heat and Mass Transfer during Drying of Red Beetroot - Zhanna Petrova; Kateryna Samoilenko; Vitaly Vishnevsky (Energy Engineering and Control Systems, 2020)
Red beetroot is the main raw material which has a high content of betanine with antioxidant properties. An important emphasis in the processing of antioxidant raw materials by drying is to reduce energy consumption for the dehydration process, the maximum preservation of biologically active substances, and to reduce the cost of the final product. Drying is a complex and energy-intensive process. Therefore, to optimize energy consumption during drying and selection of rational modes of dehydration, it is necessary to apply the calculated analysis of heat and mass transfer on the basis of adequate mathematical models. Calculated and experimental results are compared. In general, the comparison of the results of numerical modeling of convection drying processes of the red beetroot sample with the experimental results showed their rather satisfactory qualitative agreement. The calculation model can be used to approximate the characteristics of the drying process of red beetroot, in particular the time required for drying. The obtained results of calorimetric studies allow stating that with correctly selected compositions, not only the components of native raw materials are stabilized, but also the drying process is intensified with the reduction of energy consumption to process.